ANALYSIS OF RAINY DAYS AND RAINFALL TO LANDSLIDE OCCURRENCE USING LOGISTIC REGRESSION IN PONOROGO EAST JAVA - Dihin Muriyatmoko; Sisca Mayang Phuspa (Department of Geography Education, University of Jember, 2018)
Referred to data of Badan Nasional Penanggulangan Bencana (BNPB) and Kementerian Kesehatan Republik Indonesia (Kemenkes RI), almost landslide occurrence in Ponorogo always starts with high-intensity rain. This research aimed to determine simultaneously correlation and partial assessment impact of rainy days every month and monthly rainfall toward landslide occurrence in Ponorogo using logistic regression. The data collection was conducted through Badan Pusat Statistik (BPS) in the book of Ponorogo Regency in Figure on 2012 to 2016. The existing data shows that in sixty months have been twenty-six times landslides occurrence in Ponorogo districts. The data statistically analyzed in simultaneous proves that contribution of rainy days and rainfall to landslide were included adequate correlation (Nagelkerke R Square = 25.4 % and Cox & Snell R Square = 36.9 %) and in partial test proves that rainy days have significant impact (sig. = 0.024) and rainfall does not significant impact (sig. = 0.291) (Î± = 0.05) to landslide occurrence in Ponorogo regency. The rainy days per month were abled applied to predict for possible landslide elsewhere. Keywords: rainy days, rainfall, landslide, Ponorogo, logistic regression References Aditian, A., Kubota, T., & Shinohara, Y. (2018). Geomorphology Comparison of GIS-based landslide susceptibility models using frequency ratio , logistic regression , and arti fi cial neural network in a tertiary region of Ambon , Indonesia. Geomorphology Journal, 318, 101â€“111. https://doi.org/10.1016/j.geomorph.2018.06.006 Agresti, A. (1996). An Introduction to Categorical Data Analysis. Wiley. https://doi.org/10.1002/0470114754 Amri, M. R., Yulianti, G., Yunus, R., Wiguna, S., Adi, A. W., Ichwana, A. N., â€¦ Septian, R. T. (2016). Risiko Bencana Indonesia. Jakarta: Badan Nasional Penanggulangan Bencana. Badan Nasional Penanggulangan Bencana. (2018). Data Pantauan Bencana. Retrieved June 21, 2018, from http://geospasial.bnpb.go.id/pantauanbencana/data/index.php Badan Perencanaan Pembangunan Daerah Ponorogo. (2013). Pembangunan Ponorogo Dalam Angka 2013. Ponorogo. Retrieved from https://ponorogokab.bps.go.id/publication/ Badan Perencanaan Pembangunan Daerah Ponorogo. (2014). Pembangunan Ponorogo Dalam Angka 2014. Ponorogo. Retrieved from https://ponorogokab.bps.go.id/publication Badan Pusat Statistik Kabupaten Ponorogo. (2015a). Ponorogo Dalam angka 2015. Ponorogo. Retrieved from https://ponorogokab.bps.go.id/publication Badan Pusat Statistik Kabupaten Ponorogo. (2015b). Ponorogo Dalam angka 2017. Ponorogo. Retrieved from https://ponorogokab.bps.go.id/publication Badan Pusat Statistik Kabupaten Ponorogo. (2016). Ponorogo Dalam angka 2016. Ponorogo. Retrieved from https://ponorogokab.bps.go.id/publication Chuang, Y. C., & Shiu, Y. S. (2018). Relationship between landslides and mountain developmentâ€”Integrating geospatial statistics and a new long-term database. Science of the Total Environment Journal, 622â€“623, 1265â€“1276. https://doi.org/10.1016/j.scitotenv.2017.12.039 Chuang, Y., & Shiu, Y. (2018). Science of the Total Environment Relationship between landslides and mountain development â€” Integrating geospatial statistics and a new long-term database. Science of the Total Environment Journal, 622â€“623, 1265â€“1276. https://doi.org/10.1016/j.scitotenv.2017.12.039 Departemen Pekerjaan Umum. Pedoman Penataan Ruang Kawasan Rawan Bencana Longsor, Pub. L. No. 22 /PRT/M/2007, 148 (2007). Indonesia: Menteri Pekerjaan Umum Republik Indonesia. Retrieved from landspatial.bappenas.go.id/komponen/peraturan/the_file/permen22_2007.pdf%0A Hosmer, D. W., & Lemeshow, S. (2005). Multiple Logistic Regression. In Applied Logistic Regression (pp. 31â€“46). Hoboken, NJ, USA: John Wiley & Sons, Inc. https://doi.org/10.1002/0471722146.ch2 Kementerian Kesehatan Republik Indonesia. (2018). Pusat Krisis Kesehatan Kementerian Kesehatan Republik Indonesia. Retrieved June 11, 2018, from http://pusatkrisis.kemkes.go.id/ Lin, G., Chang, M., Huang, Y., & Ho, J. (2017). Assessment of susceptibility to rainfall-induced landslides using improved self-organizing linear output map , support vector machine , and logistic regression. Engineering Geology Journal, 224(May), 62â€“74. https://doi.org/10.1016/j.enggeo.2017.05.009 Logar, J., Turk, G., Marsden, P., & AmbroÅ¾iÄ, T. (2017). Prediction of rainfall induced landslide movements by artificial neural networks. Journal of Natural Hazards and Earth System Sciences Discussions, (July), 1â€“18. https://doi.org/10.5194/nhess-2017-253 Paimin, Sukresno, & Pramono, I. B. (2009). Teknik Mitigasi Banjir dan Tanah Longsor. (A. N. Ginting, Ed.). Balikpapan: Tropenbos International Indonesia Programme. Retrieved from www.tropenbos.org Pourghasemi, H. R., & Rahmati, O. (2018). Prediction of the landslide susceptibility: Which algorithm, which precision? Catena Journal, 162(November), 177â€“192. https://doi.org/10.1016/j.catena.2017.11.022 Reed, P., & Wu, Y. (2013). Journal of Fluency Disorders Logistic regression for risk factor modelling in stuttering research à¬. Journal of Fluency Disorders, 38(2), 88â€“101. https://doi.org/10.1016/j.jfludis.2012.09.003 Ubechu, B. O., & Okeke, O. . (2017). Landslide: Causes, Effects and Control. International Journal of Current Multidisciplinary Studies, 3(03), 647â€“663. Yuniarta, H., Saido, A. P., & Purwana, Y. M. (2015). Kerawanan Bencana Tanah Longsor Kabupaten Ponorogo. Jurnal Matriks Teknik Sipil, 3(1), 194â€“201. Copyright (c) 2018 Geosfera Indonesia Journal and Department of Geography Education, University of Jember Copyright Notice This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License